Program Upgrading Communication Skill Melalui Pelatihan Berpidato Bagi Pelajar Taman AL-Qur’an Hulu Kelang, Malaysia - Al Farizi, Salman; Ramadhani, Jennifer Sakti; Fatimatuzzahro, Rhiznindya; Faathima, Faathima (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
Community Service Activities or what are called International Real Work Lectures by Darussalam Gontor University students will be held in Malaysia, precisely at the Guidance Studio which the Embassy of the Republic of Indonesia in Malaysia supervises. This activity will be carried out for 10 days starting from March 10 2024 to March 20 2024. This guidance studio was chosen as the location to apply KKN activities because it has students from Indonesia. KKN activities begin with assistance to hone the communication skills of the Guidance Studio children with speech training. Various learning methods and speech training are applied during KKN activities, including providing a pocketbook with a collection of speech texts to make the learning process easier for children. The implementation of the KKN program is carried out in appropriate stages starting from planning, implementation and evaluation after the activity program takes place. Implementing the Communication Skill Upgrading Program is structured and adapted to the needs of the Guidance Studio. It is hoped that the results of this KKN activity will improve communication skills through speech training in three languages, namely Indonesian, English and Arabic.